2023
DOI: 10.3390/clinpract13040070
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Glutathione Antioxidant Pathways in the Pathophysiology and Adjunct Treatment of Psychiatric Disorders

Abstract: Oxidative stress is defined as the imbalance between the production of free radicals and their removal by antioxidants, leading to accumulation and subsequent organ and tissue damage. Antioxidant status and its role in the accumulation of free radicals has been observed in a number of psychological disorders. Glutathione is commonly referred to as the principal antioxidant of the brain and, therefore, plays a critical role in maintaining redox homeostasis. Reduced levels of glutathione in the brain increase it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Interestingly, a recent longitudinal study has demonstrated that an increase in glutathione levels was associated with less increase in the probability of prodromal PD [135]. Glutathione-related signaling pathways have been related to the development and progression of several psychiatric disorders, including depression, anxiety, and schizophrenia [136]. Further studies should also focus on the relationship between glutathione levels and MBI in PD.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…Interestingly, a recent longitudinal study has demonstrated that an increase in glutathione levels was associated with less increase in the probability of prodromal PD [135]. Glutathione-related signaling pathways have been related to the development and progression of several psychiatric disorders, including depression, anxiety, and schizophrenia [136]. Further studies should also focus on the relationship between glutathione levels and MBI in PD.…”
Section: Future Perspectivesmentioning
confidence: 98%